Biological pretreatment: An innovative approach to addressing taste and odor. Issue 2 (9th March 2020) - Brown, Jess; Nyfennegger, Jennifer; Ang, Yong; Simpson, Mark; MacLeod, Bruce; Wolanin, Olga; Gilmore, Katherine
Abstract: The presence of objectionable taste‐and‐odor (T&O) compounds in surface water supplies is a common problem facing drinking water utilities across the country and worldwide. While there are several viable T&O treatment options, including adsorption, biotransformation, and advanced oxidation, no single option fits all applications or is without potential limitations. Through bench‐ and pilot‐scale testing, this work developed and evaluated high‐rate biological roughing filtration as a promising alternative for geosmin and 2‐methylisoborneol abatement to help utilities minimize T&O complaints without straining their annual operating budgets. Testing showed that biological roughing filtration can effectively treat a wide range of raw water T&O levels using short contact times, and the intermittent presence of T&O compounds did not appear to appreciably affect removal efficacy. Pilot‐testing results were used to develop the design criteria for a full‐scale 54‐mgd biological roughing filter that is currently treating surface water in Manatee County, Florida.